Adaptasi Usaha Mikro, Kecil, dan Menengah (UMKM) Bandeng Presto Selama Masa Pandemi Covid-19: Studi Kasus di Kota Semarang - Ch. Retnaningsih; Berta Bekti R; Okti Ruenda (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Retnaningsih Ch, Bekti RB, Ruenda O. 2020. Adaptation of Presto Milkfish Small and Medium Enterprises (SMEs) during the covid-19 pandemic: a case study in Semarang city. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. 1-11. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Presto milkfish is one of the processed seafood product produced by SMEs in the city of Semarang. A case study conducted on 30 samples of SME processed seafood aims to determine the adaptations during the Covid-19 pandemic. The case study method is carried out by surveying the production location of SMEs. From the results of this case study, it was found that out of 18 samples of SMEs that produced presto milkfish, 72% had adapted their business in various ways such as product development innovation to improve quality. The number of samples of SMEs that innovated was 50%, and those that did not innovate on the products produced were 50%. Business adaptation by presto milkfish SMEs needs to be done for business continuity during the Covid-19 pandemic.